2014
DOI: 10.4161/mabs.36252
|View full text |Cite
|
Sign up to set email alerts
|

Remediating agitation-induced antibody aggregation by eradicating exposed hydrophobic motifs

Abstract: Therapeutic antibodies must encompass drug product suitable attributes to be commercially marketed. An undesirable antibody characteristic is the propensity to aggregate. Although there are computational algorithms that predict the propensity of a protein to aggregate from sequence information alone, few consider the relevance of the native structure. The Spatial Aggregation Propensity (SAP) algorithm developed by Chennamsetty et. al. incorporates structural and sequence information to identify motifs that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Previous examples of antibody re-engineering to improve stability have reported significant reductions in affinity when the problematic residues are located in the CDRs152035. Analysis of the crystal structure of MEDI1912’s parental antibody, MEDI-578, in complex with NGF indicates, however, that the three residues described here do not interact directly with NGF and hence their substitution does not impact binding affinity.…”
Section: Discussionmentioning
confidence: 82%
“…Previous examples of antibody re-engineering to improve stability have reported significant reductions in affinity when the problematic residues are located in the CDRs152035. Analysis of the crystal structure of MEDI1912’s parental antibody, MEDI-578, in complex with NGF indicates, however, that the three residues described here do not interact directly with NGF and hence their substitution does not impact binding affinity.…”
Section: Discussionmentioning
confidence: 82%
“…Clark et al 133 have also used homology modeling and SAP calculations to design variants of a highly aggregation-prone IgG2; mutational positions were chosen based on the SAP scores, whereas the selection of the types of substitutions was based on the sequence comparison to an aggregation-resistant homologue, which resulted in 74 variants with as many as 9 mutations. The resultant variants showed enhanced conformational and colloidal stability in 32 cases, out of which 11 variants could still bind to the antigen, as confirmed by SPR, and 9 variants showed biological activity, as confirmed by an assay using natural killer cells.…”
Section: Spatial Aggregation Propensitymentioning
confidence: 99%
“…Multiple publications have shown that modification of residues within the Fv region can increase the conformational stability of the Fab [20][21][22]24,53,54 with greater increases associated with multiple modifications. Here we specifically targeted residues in the framework regions 1-4 using a purely computational approach based on the method of Gunasekaran et al 31 to determine which could potentially destabilize the domain.…”
Section: Discussionmentioning
confidence: 99%
“…While COGs can be severely reduced using small-scale and highcapacity flexible facilities, 18 the antibodies must also be sequence optimized for manufacturability because even minor changes can affect productivity and ease of purification. 19,20 Multiple publications have demonstrated that the amino acid sequence of the constant and variable regions of antibodies can affect molecular stability, expression levels, downstream processing conditions, and formulation conditions required for stable longterm storage. [19][20][21][22][23][24][25][26][27] Clark et al 20 demonstrated that introduction of multiple amino acid substitutions into the Fv region of an IgG2 to alter the amount of exposed hydrophobic and hydrophilic surface areas resulted in an increased titer that correlated with an increase in the thermal stability of the variants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation